The impact of intelligent manufacturing on industrial green total factor productivity and its multiple mechanisms - Yang, Zhihong; Shen, Yang (Frontiers in Environmental Science, 2023)
As an integration of artificial intelligence (AI) and advanced manufacturing technology, intelligent manufacturing has realized the innovation of manufacturing mode and created conditions for the green development of the industry. After constructing the theoretical framework between intelligent manufacturing and industrial green total factor productivity (GTFP), this paper first uses the panel data of 30 provinces in China from 2006 to 2020, and expresses the level of intelligent manufacturing with industrial robot density. Then, economic effect and mechanism are discussed by using the interactive fixed effect model, mediating effect model and moderating effect model. The panel quantile regression model shows that the influence of intelligent manufacturing on industrial GTFP has an increasing marginal effect. With the quantile points goes from low to high, the coefficient and statistical significance become larger. Human capital is the mechanism for intelligent manufacturing to improve industrial GTFP. Green technology innovation and producer service industry agglomeration have strengthened the positive effect of intelligent manufacturing on industrial GTFP. There is also heterogeneity in the effect of intelligent manufacturing on industrial GTFP, and the stronger the effect in the pilot areas of carbon emission trading policy and industrial green transformation development policy. In order to give full play to the technological dividend and empower sustainable industrial development, the paper argues that we need to accelerate the integration of AI and manufacturing technology, thus improving the level of industrial intelligence, and empowering green development.